Адаптивное подавление помех в системах акустического зондирования - Чернов, К. А.; Воронин, В. В. (ХНУРЕ, 2019)
The spectrums of acoustic noise are investigational of the system of the acoustic sounding of atmosphere. The estimations of frequency of spectrum peak are found at adaptive suppression noise.